Staff retention factors in the non-profit sector: An examination of a West Australian community organization - Colleran, N.; Gilchrist, David; Morris, C. (Australian and New Zealand Third Sector Research Inc., 2010)
In Australia today, non-profit organisations, like most other entities, are trying to respond effectively to challenges associated with the recruitment and retention of competent, experienced and committed staff. Unlike government and commercial entities, however, the poor resourcing of non-profit organisations makes it necessary to approach the issue of recruitment and retention with more creativity than what perhaps is required of organisations in the other two sectors of the Australian economy. This is particularly the case for non-profit organisations operating in Western Australia, where the economic conditions – based on resource exploitation – make recruitment and retention, even in the context of the recently reduced economic activity in the state, extremely difficult. This article seeks to communicate the results of a study that focused upon the retention factors that staff considered to be important in a non-profit organisation based in the northern periphery of Perth, Western Australia.